Analysis of Assertive Illocutionary Acts in the Movie Titled Up - Putu Agus Kurnia Ary Pratama (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research analyzes assertive illocutionary acts contained in the dialogue of the animated film "Up". Illocutionary acts, namely the actions intended to be carried out by an utterance, are an important aspect in pragmatics and speech act theory. This researcher used a qualitative descriptive approach to closely examine the language used by characters in the film and identify assertive illocutionary acts that convey information or make statements. Film scripts are the main data source in this research. This research uses theories from Searle and Halliday to answer questions from the research conducted. By analyzing representative illocutionary acts in dialogue, the research aims to provide insight into the themes, communication goals, and power dynamics present in the narrative of the film "Up". These findings contribute to a better understanding of how language is used to advance plots and develop characters in animated films.